FAKTOR-FAKTOR YANG MENENTUKAN EKSISTENSI MORFOLOGI KAMPUNG PEKOJAN SEMARANG SEBAGAI KAMPUNG MULTI ETNIS - Wahjoerini Wahjoerini (Jurnal Riptek, 2019)
Semarang is one of the major cities in Indonesia that borders on the Java and  one of  the city in Central Java that its development is largely influenced by function as a port city since the colonial. This led to a large number of acculturation between cultures with indigenous migrants. One of the old village in Semarang that is characterized as a multi ethnic villages namely is Kampung Pekojan. The village is  Kampong Pekojan in Semarang. The village at Purwodinatan, Semarang Central which runs from the intersection of JL. Agus Salim (formerly Jurnatan) to the South. Pekojan  taken from the name ' Koja' is a region in Western India, which a lot of wandering and settled in this area. Kampung Pekojan consists of three different ethnic, namely Chinese, Koja and Java. In addition, in the village there is a mosque pekojan still believed to be the relics of the ancestral city of Semarang. Citizens maintain ancestral traditions as Pekojan reference. With the development of the city of Semarang growing bolder leaps and bounds, then developed the village Pekojan. The problems that exist among them that Pekojan building followed by changes in function, with the development, then change morphology Kampung Pekojan. Morphological changes in Kampung Pekojan can be seen from the building that is the origin of the mosque which is inseparable from the history of the area of Kampung Pekojan, so  research to understanding anything which determines the existence of the village. In addition, the emergence of commercial activity and Services strongly influenced the development of the village because the event is for the communities.Purpose of doing research is to know the existence of the morphology of Kampung Pekojan  Semarang along with the development of the city of Semarang. The benefits of the research done by defending the existence of the people living there were able to survive and the village became the city of Kampong  Pekojan in place and can be used to provide input to the local governments in the region in the city of Semarang.The methods used in this research uses qualitative descriptive analysis. The Output of research of the factors that determine the existence of the morphology of them namely Kampung Pekojan in Semarang structures still existing in the original Kampung Pekojan Semarang, the function as well as the village tradition is still maintained.